Water Governance Management During Drought in East Nusa Tenggara: An Evaluation of Clean Water Distribution and the Role of Local Government - Riszqi Bahtiar Alam; Agus Setio Widodo (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
Due to a combination of geographic factors, low rainfall, prolonged dry seasons, and the effects of global climate anomalies such as El Niño, chronic drought is worsening in East Nusa Tenggara (NTT) Province. This situation impacts communities in various ways, including limited access to clean water, decreased agricultural productivity, food insecurity, increased health risks, and a disproportionate socioeconomic burden on women and children. This study found that there is a structural gap between local government distribution capacity and community water needs. This gap is caused by limited infrastructure, poor inter-agency coordination, unstable funding, and a lack of integration of climate data into water governance planning. Based on the results, this study recommends the use of an integrative and adaptive approach to improve water governance. It is hoped that implementing these policy recommendations will increase community resilience to drought and provide support to developers and communities in water resource management. These policy recommendations also include the implementation of an integrated water security information system, the establishment of a multi-sectoral coordination team, the development of water infrastructure responsive to local ecological conditions, and the implementation of an early response funding mechanism based on climate forecasts.